Modeling the process of risk management response to the negative impact of risks as the basis for ensuring economic security - Kryshtanovych, Svitlana; Gutsulyak, Viktoriya; Huzii, Ivanna; Helzhynska, Tetiana; Shepitchak, Valentyna (Business, Management and Economics Engineering, 2021)
Purpose – the main purpose of the article is to form a methodological approach to counteract risks that most negatively affect the system of ensuring the economic security of engineering enterprises.Research methodology – the research methodology involves the application of the theory of graph connections, modeling from IDEF0.Findings – the main risks that most negatively affect the system of ensuring the economic security of engineering enterprises were identified, modeling of the main stages of response to their impact was carried out.Research limitations – the article has a number of limitations and this applies to the area of the study. The emphasis was on the engineering industry. In addition, it should be noted that there are other modeling methods for mapping the stages of response to the negative impact of risks.Practical implications – practical application of our methodological approach can be suitable for engineering enterprises.Originality/Value – the originality of the study lies in the presented methodological approach to identifying the risks that most negatively affect the system of economic security of engineering enterprises and modeling the process of responding to this impact.